BIOECOPHYSIOLOGICAL AND ADAPTIVE PROPERTIES OF DESERT PLANTS UNDER CONDITIONS OF GLOBAL CLIMATE CHANGE - Kholliyev Askar Ergashovich; Norboeva Umida Toshtemirovna (Modern American Journals, 2025)
The article presents comprehensive research on the ecological status of natural pastures in the Karakul district of the Bukhara region, Uzbekistan. It examines the causes and consequences of pasture degradation due to overgrazing, climate change, and unsustainable land use practices. The authors analyze the current dynamics of desert ecosystems and propose practical measures aimed at mitigating degradation through the rational use and restoration of pasture lands. Particular emphasis is placed on the importance of maintaining ecological balance, conserving biodiversity, and applying phytomeliorative methods to rehabilitate degraded lands. The study concludes that desert pasture ecosystems demonstrate a certain degree of resilience to climate variability, which can be strengthened through informed management strategies and the integration of traditional and scientific knowledge.
Keywords: Pastures, grazing, degradation, desert, ecosystems, plant associations, phytomelioration, sustainable land use, climate resilience.